Exclusivism Reduces Empathy in Community Life in Satellite Cities - R. Mita Resmi Husara; Veithzal Rivai Zainal; Azis Hakim (Dinasti International Journal of Education Management And Social Science, 2025)
Bekasi is one of the satellite cities of DKI Jakarta, and its population is very heterogeneous. The diversity of character of the population, educational background, culture, and mobility is fascinating to study more deeply. If it is associated with the social side, we will find the phenomenon of exclusivity of the residents. This study examines the phenomenon of social exclusivism, which reduces empathy in the social order in Bekasi City. The study aims to identify the factors that cause exclusivism and provide related solutions. Using qualitative descriptive methods, data were obtained through interviews, observations, and documentation with informants from various levels of society. The study's findings show that high work mobility, differences in social strata, and technological developments worsen social relationships between citizens, decreasing empathy. This research contributes to enriching the literature on exclusivism and empathy and provides recommendations for social policies and character education to increase social solidarity in satellite cities.